Febrile convulsion: review and update - Daoud, Azhar (Journal of Pediatric Neurology, 2004)
Febrile convulsions (FCs) are the most frequently occurring epilepsy syndrome experienced in infants/children between 6 months and 6 years of age and occur in 2–4%. It describes any seizure that occurs in response to a febrile stimulus in the absence of meningitis, encephalitis, serum electrolyte imbalance and other acute neurologic illnesses. There have been many recent reports on the molecular genetic and pathogenesis of FC. It has been recognized that there is significant genetic component for susceptibility of FC with different reported mutation. Others have tried to correlate FC to immunologic problem through interleukin, cytokines, immunoglobulin and interferon. Also, reports on correlations between FC and iron deficiency anemia, hypozincemia or to specific infections have been published. Children having first or second degree relatives with a history of FC, neonatal nursery stay of more than 30 days, developmental delay or attendance at a day care center are at increase risk of developing FC. A single simple FC does not seem to increase the risk of epilepsy and there is no causal relationship between FC and subsequent epilepsy. Viruses are the most common cause of illness in children admitted to the hospital with a first FC. Routine laboratory studies, electroencephalogram and neuroimaging are not indicated for patients who have FC, and should be performed only as part of the evaluation for a source of fever and/or in atypical cases. Prognosis is generally good and parents should be counseled about the benign nature of FC. Children with FC are at no greater risk of intellectual impairments than their peers. Maintenance therapy to prevent recurrence has not been shown to prevent later development of epilepsy, and therefore intermittent diazepam or lorazepam are the main drugs to be used. (J Pediatr Neurol 2004; 2(1): 9–14).
Keywords: febrile convulsion; review; update